2018
DOI: 10.1111/nyas.13582
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness clinical trials to advance treatment of myasthenia gravis

Abstract: Myasthenia gravis (MG) presents many challenges for establishing treatment efficacy through clinical trials. Among these are the rarity and heterogeneity of the disease, spontaneous fluctuations, prolonged latency to effect for many immunosuppressive drugs, and the uncertain generalizability of results from randomized controlled trials (RCTs). Prospective observational study designs may overcome some of these limitations, but attention is required to ensure that internal validity is not compromised. Observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…1,2 However, data assessing generalizability of trial results to clinical practice are limited. 3 In this study, we reviewed clinical response, change in immunomodulatory therapy (IMT), and adverse events in patients at two academic centers who received eculizumab for AChR+ gMG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, data assessing generalizability of trial results to clinical practice are limited. 3 In this study, we reviewed clinical response, change in immunomodulatory therapy (IMT), and adverse events in patients at two academic centers who received eculizumab for AChR+ gMG.…”
Section: Introductionmentioning
confidence: 99%
“…The REGAIN clinical trial and its open‐label extension (OLE) demonstrated eculizumab's efficacy and favorable safety profile for the treatment of acetylcholine receptor antibody positive (AChR+) generalized myasthenia gravis (gMG) 1,2 . However, data assessing generalizability of trial results to clinical practice are limited 3 . In this study, we reviewed clinical response, change in immunomodulatory therapy (IMT), and adverse events in patients at two academic centers who received eculizumab for AChR+ gMG.…”
Section: Introductionmentioning
confidence: 99%